Follow-Up Queue Impact Due to The Closures of Perintis Kemerdekaan Railroad Crossing on Vehicle Velocity Decrement of Gatot Subroto Street - Sugendra, Renaldy; Putra, Sasana; Ofrial, Siti Anugrah Mulya Putri; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
The closures of railroad crossing on Perintis Kemerdekaan Street frequently cause vehicle queues on Gatot Subroto Street. The density that happens on Perintis Kemerdekaan Street impacts on the occurrence the road constringency and vehicle velocity delay. The results with four hours of observation, the delay values can be concluded with shockwave analysis. 20,72 km/h is determined as for the value of forwarding forming shockwave (ωda) in morning observation and 9,08 km/h in the afternoon; with 1,32 km/h of backward forming shockwave (ωab) in the morning and -1,07 km/h in the afternoon; also forward recovery shockwave (ωdc) in the morning is 5,17 km/h and 1,98 km/h in the afternoon; as well with -10,64 km/h as the value for backward recovery shockwave (ωcb) in the morning and -4,10 km/h in the afternoon; as for the frontal stationary shockwave (ωac) the value is 4,73 km/h in the morning and 1,75 km/h in the afternoon. The mileage time increment is up from 4,25 to 7,6925 seconds in the morning and from 10,68 to 21,196 seconds in the afternoon.